Avaliação retrospectiva de pinos pré fabricados cimentados nas clínicas de prótese dental da UFSM - Trindade, Rodrigo Farcili (2010)
The objective of this retrospective study was to assess the clinical performance over time of direct cores supported by prefabricated posts and cemented at the UFSM Dental Prosthetics Clinics between 1997 and 2007, as part of the restorative treatment proposed for patients with significant losses to coronary structures. After approval had been granted by the Research Ethics Committee at the UFSM, 191 patients, from a total of 321 patients, who had been treated with metalceramic restorations cemented onto direct cores, and for whom full address details were available, were invited to take part by letter or by telephone. Sixty-one of these patients were investigated for this study. Clinical and radiographic examinations were carried out at the UFSM dental prosthetics clinic by four trained examiners. A descriptive analysis of the data collected was performed using STATA 9.0. The success rate of the treatments carried out was 96.38%, since 80 of the 83 teeth were still in place. The post-core assemblies were still in place in 96.38% of the treated teeth and 97.59% of the roots were intact. The percentage of crown restorations still intact was the same as for the teeth: 96.38% (80), with 72.5% (58) being single metal-ceramic crowns and 27.5% (22) fixed bridge pillars. At the time of data collection, the mean survival time for the single metalceramic restorations was 5.68 years (±3.28), while the fixed bridges had been in place and functional for 5.09 years (±2.97). Fiberglass prefabricated posts had a mean survival of 4.45 years (+3.14); and the metal posts survived 7 years (+2.67). The success rate observed in this study (96.38% to 97.59%) confirms the hypothesis that restorative technique of treating teeth endodontically with direct root canal retention and prefabricated posts is both safe and clinically applicable.